CORRELATION OF SNACKING FREQUENCY, HEMOGLOBIN LEVELS, PHYSICAL ACTIVITY AND POCKET MONEY WITH NUTRITIONAL STATUS IN FEMALE ADOLESCENTS - Dinar Putri Rahmawati; Dono Indarto; Diffah Hanim (Media Gizi Indonesia, 2021)
Nutritional problem that occurs in adolescents due to higher food intake and less physical activity leads to over- nutrition. Other nutritional problems occur among them is micronutrient deﬁciency including anemia, mostly in female adolescents. Higher consumption of energy-dense snacks, low physical activity and more pocket money  have contributed to adolescent’s body weight. This study aims to determine the correlation of frequency of snacking, hemoglobin levels, physical activity, and pocket money with the nutritional status of female adolescents. This cross- sectional study was carried out in 117 female adolescents in Karanganyar Regency, Central Java Province. Data of snacking frequency was collected using the Food Frequency Questionnaire (FFQ) and hemoglobin level were measured using a Hematology Analyzer. Physical activity data were collected using the IPAQ questionnaire (International Physical Activity Questionnaire) and were converted to Metabolic Equivalent Tasks (METs). Normally distributed data then analyzed using Pearson test and Spearman test for not normally distributed data to determine correlation between independent with dependent variables and followed by the multiple linear regression test if the p-value < 0.25. Most female adolescents had normal nutritional status, but 6.8% and 17.9% female adolescents were overweight and obesity, respectively. The frequency of snacking (r = 0.207, p = 0.025), physical activity (r = -0.201, p = 0.030), pocket money (r = 0.283, p = 0.002) and hemoglobin level (r = 0.150, p = 0.107) were not correlated with nutritional status. In conclusion, frequency of snacks, physical activity, and pocket money were signiﬁcantly correlated with nutritional status in female adolescents but no correlation with hemoglobin level.